2017
DOI: 10.5799/jcei.333383
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Nurses' Empathy Skills on Attitudes towards Patients with Cancer

Abstract: Objective: The purpose of this study is to evaluate the predictors of empathy skills and attitude towards cancer patients and association between nurses' empathy skills on attitudes towards patients with cancer Patients and Methods: A structured questionnaire was used to evaluate the nurses' empathy skills and their attitudes towards to patients with cancer. Jefferson Scale of Empathy (JSE) and Attitudes towards Cancer Scale (ATCS) were used. The predictors of JSE/ATCS scores and correlation between JSE and AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It is very important for the nurses, providing care to the individuals diagnosed with cancer receive the training during their education, to provide to develop positive attitudes and provide care from this point of view upon their graduation. If the attitude toward cancer is extremely negative, the outcomes of patients may be affected negatively however it is observed that the nursing education is not structured enough in this sense (7,8,18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important for the nurses, providing care to the individuals diagnosed with cancer receive the training during their education, to provide to develop positive attitudes and provide care from this point of view upon their graduation. If the attitude toward cancer is extremely negative, the outcomes of patients may be affected negatively however it is observed that the nursing education is not structured enough in this sense (7,8,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Usta et al stated in their study that nurses were aware of the effect of displaying positive attitudes for cancer patients (18). It was observed in the study conducted by Alkan with nurses that the nurses, who received the training on cancer, provided care to cancer patients, and had a cancer history in their close relatives, had more positive attitudes (19). Edwards et al pointed out that it was very difficult to develop positive attitudes toward cancer in nursing students; however, this may be possible by integrating cancer education into nursing education (20).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering that establishing professional relationships is a necessary principle for providing nursing care and as one of the most important causes of anxiety in the nursing profession is lack of a good working relationship with their colleagues, determining the barriers to establish effective relationships between the nurses could help develop more effective interventions and programs for resolving the barriers and facilitating the communications. Further, by executing communicational skills development programs, the level of communicational skills would be improved in the nurses (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…A dissertation that was a quantitative study by Burns [17] was reviewed as this initial research has been used as a tool to measure knowledge and attitudes toward cancer. Two tools by Burns [17] and Haley [18] were used in subsequent studies [3,[17][18][19][20][21][22].…”
Section: Data Evaluation and Analysismentioning
confidence: 99%
“…Cancer affects a patient's daily life and can affect the ability to cope with the effects of illness and treatment side effects [2]. Studies have been conducted to understand the perspectives of health care professionals regarding the needs of patients with cancer or their attitudes that can be used to improve patient care and quality of life [3][4][5][6][7][8][9]. Nurses play a vital role in providing quality care to patients with cancer.…”
Section: Introductionmentioning
confidence: 99%